2017
DOI: 10.1007/s10666-017-9559-1
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Framework for Assessing Physical and Wildlife Impacts of Oil and Gas Development Scenarios in Southwestern Wyoming

Abstract: Foreseeable natural gas development in southwestern Wyoming has the potential to increase sagebrush fragmentation and risks to resident wildlife species. The ability to balance future development with conservation goals, however, is enhanced by advances in directional-drilling technologies that use multiple wells per pad and produce less surface disturbance than conventional drilling methods. To evaluate the conservation potential of this technology, I developed an energy footprint model that simulates well, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…These results, and those presented by Gamo and Beck (2017), support the conclusion that overall the Wyoming Governor's Executive Order is helping safeguard critical sagegrouse habitats at the State-wide scale. Other recent research is consistent with past findings that the implementation of certain mitigation techniques or design features for oil and gas operations may be beneficial in reducing, but not eliminating, adverse effects to sage-grouse (Fedy and others, 2015a;Garman, 2017;Holloran and others, 2015;Kirol and others, 2015b).…”
Section: Oil and Gas Developmentsupporting
confidence: 83%
“…These results, and those presented by Gamo and Beck (2017), support the conclusion that overall the Wyoming Governor's Executive Order is helping safeguard critical sagegrouse habitats at the State-wide scale. Other recent research is consistent with past findings that the implementation of certain mitigation techniques or design features for oil and gas operations may be beneficial in reducing, but not eliminating, adverse effects to sage-grouse (Fedy and others, 2015a;Garman, 2017;Holloran and others, 2015;Kirol and others, 2015b).…”
Section: Oil and Gas Developmentsupporting
confidence: 83%
“…We used a spatially explicit oil and gas footprint model (Garman ) to simulate realistic spatial patterns of future oil and gas development under alternative development intensity scenarios. The model annually added new well pads and access roads to existing oil and gas infrastructure, cumulating active infrastructure over 50 yr (2012–2062).…”
Section: Mapping Habitat Impactsmentioning
confidence: 99%
“…Both energy development and climate-driven conversion of sagebrush vegetation (Artemesia spp.) are expected to affect Greater Sage-grouse (hereafter Sagegrouse) populations over the next 50 yr (Homer et al 2015, Garman 2018), yet we know little about their potential magnitudes and combinatory influences on populations. Southwest Wyoming (Wyoming Landscape Conservation Initiative area covering five counties, hereafter SW WY) hosts a large population of Sage-grouse that depend on sagebrush landscapes for their seasonal habitat needs.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Related modeling efforts have demonstrated that much more detailed modeling of surface disturbances from energy development is feasible. Garman (2015Garman ( , 2018 describes an "energy footprint" model in which actual well pad and road networks from recent development in a region of interest are digitized and then sampled within a simulation framework to make more realistic predictions of what the surface disturbance for a given development buildout would look like on the ground. This computationally intensive approach provides fine-grained information that is likely to be more useful in detailed ecological modeling than simpler aggregated approaches.…”
Section: Integrated Dynamic Models-synthesis Of Previous Effortsmentioning
confidence: 99%